1999
DOI: 10.1002/(sici)1097-0215(19990531)81:5<813::aid-ijc24>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Role of NK and T cells in IL-12-induced anti-tumor response against hepatic colon carcinoma

Abstract: IL‐12 is an immuno‐regulatory cytokine that has been shown to generate a potent NK and Th1 response in a variety of laboratory models. However, the detailed immune development in the hepatic tumor model by IL‐12‐mediated gene therapy has not been clarified. In our previous study, intra‐tumoral transfer of Adv.mIL‐12 (5 × 108 pfu) to the MCA26 colon carcinoma liver tumor induced an effective anti‐tumor response, extending the median survival time from 29 to over 54 days, while 25% of the animals became tumor‐fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 27 publications
4
53
1
1
Order By: Relevance
“…6 In addition to NK cells, we have shown that T cell participation was mandatory to achieve persistent anti-tumor immunity, and survival of a majority of tumor-bearing animals. 9 In this study, the ability of a treatment that combined triggering of the 4-1BB costimulatory molecule, either with systemic delivery of agonistic anti-4-1BB mAb or intra-tumoral delivery of ADV/4-1BBL, and intratumoral IL-12 gene therapy was tested to induce regression of pre-established breast liver metastases and persistent anti-tumor immunity. Systemic anti-4-1BB mAb alone induced a dramatic tumor regression compared with intra-tumoral delivery of ADV/4-1BBL and adequate controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 In addition to NK cells, we have shown that T cell participation was mandatory to achieve persistent anti-tumor immunity, and survival of a majority of tumor-bearing animals. 9 In this study, the ability of a treatment that combined triggering of the 4-1BB costimulatory molecule, either with systemic delivery of agonistic anti-4-1BB mAb or intra-tumoral delivery of ADV/4-1BBL, and intratumoral IL-12 gene therapy was tested to induce regression of pre-established breast liver metastases and persistent anti-tumor immunity. Systemic anti-4-1BB mAb alone induced a dramatic tumor regression compared with intra-tumoral delivery of ADV/4-1BBL and adequate controls.…”
Section: Discussionmentioning
confidence: 99%
“…Seven days later (3 days before virus injection), in vivo CD4 + (purified ascites GK1.5 (ATCC)) or CD8 + T cell (purified ascites 2,43 (ATCC) depletion was performed using specific antibodies, as described previously. 9 Rat Ig was used in control animals after either treatment. Animals received a s.c. challenge of 1 × 10 5 JC parental cells on the flank at day 10 after the virus treatment.…”
Section: In Vivo T Cell Depletion Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although combination therapy resulted in enhanced suppression of local tumor growth, it did not produce increased animal survival in this model. Based on previous studies which suggested that NK cells are largely responsible for the antitumor effects of adenoviral vector-mediated IL-12 gene therapy 4,20 we focused on this activity. However, an investigation into other discrete therapeutic end points revealed interesting differences in AdHSV-tk GCV compared to AdmIL-12 gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that endogenous IL-12 is required not only for resistance to many pathogens but also for chemically induced tumors. Using experimental models, recombinant IL-12 was reported to have a dramatic anti-tumor effect on various tumors including esophageal cancer (Cardenes et al 2010;Mu et al 1995;Pham-Nguyen et al 1999). Moreover, genetic defects in IL-12 production have been shown to predispose individuals to EC (Cardenes et al 2010).…”
Section: Il-12mentioning
confidence: 99%